A Universal Nonhalogenated Polymer Donor for High‐Performance Organic Photovoltaic Cells. Issue 2 (1st November 2021) - Zhang, Tao; An, Cunbin; Cui, Yong; Zhang, Jianqi; Bi, Pengqing; Yang, Chenyi; Zhang, Shaoqing; Hou, Jianhui
Abstract: Nonhalogenated polymers have great potential in the commercialization of organic photovoltaic (OPV) cells due to their advantage in low‐cost preparation. However, non‐halogenated polymers usually have high highest occupied molecular orbital (HOMO) energy levels and inferior self‐aggregation properties in solution, thus resulting in low power conversion efficiencies (PCEs). Herein, two nonhalogenated polymers, PB1 and PB2, are prepared. When the polymers are used to fabricate OPV cells with BTP‐eC9, the PB1‐based device only gives a PCE of 5.3%, while the PB2‐based device shows an outstanding PCE of 17.7%. After the introduction of PBDB‐TF as the third component, the PB2:PBDB‐TF:BTP‐eC9‐based device with an optimal weight ratio of 0.5:0.5:1 achieves a PCE up to 18.4%. More importantly, PB2 exhibits good compatibility with various nonfullerene acceptors to achieve better PCEs than those of classical polymer (PBDB‐T and PBDB‐TF)‐based devices. When PB2 is combined with a wide‐bandgap electron acceptor (F‐BTA3), this device shows excellent PCE of 27.1% and 24.6% for 1 and 10 cm 2 devices, respectively, under light intensity of 1000 lux light‐emitting diode illumination. These results provide new insight in the rational design of novel nonhalogenated polymer donors for further development of low‐cost materials and broadening the application of OPV cells. Abstract : Two nonhalogenated polymers, PB1 and PB2, with different side‐chain orientations and deep highest occupied molecular orbital (HOMO) levels are reported. In organic photovoltaic (OPV) cells, PB1 only produces a power conversion efficiency (PCE) of 5.3%, while PB2 gives an outstanding PCE of 17.7%. More importantly, PB2 has good compatibility with various electron acceptors. PB2 achieves excellent PCEs of 18.4% and 27.1% for ternary OPV cells and indoor light photovoltaic devices, respectively.